Keeping the Parents outside the School Gate-A Critical Review - Carmel Kent; Benedict du Boulay; Mutlu Cukurova (MDPI AG, 2022)
The existing evidence shows that parental engagement is one of the most effective educational interventions. Most parents, carers, and teachers are aware of that and wish to engage with their children's education. However, most parents are still only peripherally involved through parent-teacher evenings, school activities, or by helping their children keep up with their homework. In this review paper, we summarize the evidence about the impact of parental engagement, as opposed to involvement, on the learning of children. Via that, we critically look at the design choice of most western mainstream public education systems to distance parents from their children's education, which, as the review results indicate, can be detrimental to children's learning. Based on these results, we reframe parental engagement in the light of two global shifts: (1) the implications of the school closures during the COVID-19 pandemic for the role of parents in their children's learning; and (2) the increased use of educational technologies for learning, and specifically, the rise of artificial intelligence (AI) technologies. We conclude by calling for a renewed conversation about parents' and families' roles in their children's learning and their interface with schools and teachers.